Motivasi Belajar Dan Hasil Belajar Siswa Pada Masa Pandemi Covid-19 - Farah Faida (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
The Covid-19 pandemic has indeed changed the daily mobility of many people, especially the education system in Indonesia which has switched to distance learning or what is usually called online. Of course, this online learning method influences student motivation and learning outcomes from the perspective of teachers, parents and students themselves. Therefore, the aim of this research is to determine student motivation and learning outcomes during online learning during the Covid-19 pandemic. The method used in this research is based on a qualitative descriptive literature review, which uses research results evaluated in publications. The findings of this research were the discovery of positive and negative influences on student learning outcomes due to differences in student motivation during online learning during the Covid-19 pandemic.